Using Standardized Interpretation of Chest Radiographs to Identify Adults with Bacterial Pneumonia--Guatemala, 2007-2012. - Jonathan M Wortham; Jennifer Gray; Jennifer Verani; Carmen Lucia Contreras; Chris Bernart; Fabiola Moscoso; Juan Carlos Moir; Emma Lissette Reyes Marroquin; Rigoberto Castellan; Wences Arvelo; Kim Lindblade; John P McCracken (PLoS ONE, 2015)
Bacterial pneumonia is a leading cause of illness and death worldwide, but quantifying its burden is difficult due to insensitive diagnostics. Although World Health Organization (WHO) protocol standardizes pediatric chest radiograph (CXR) interpretation for epidemiologic studies of bacterial pneumonia, its validity in adults is unknown.Patients (age ≥ 15 years) admitted with respiratory infections to two Guatemalan hospitals between November 2007 and March 2012 had urine and nasopharyngeal/oropharyngeal (NP/OP) swabs collected; blood cultures and CXR were also performed at physician clinical discretion. 'Any bacterial infection' was defined as a positive urine pneumococcal antigen test, isolation of a bacterial pneumonia pathogen from blood culture, or detection of an atypical bacterial pathogen by polymerase chain reaction (PCR) of nasopharyngeal/oropharyngeal (NP/OP) specimens. 'Viral infection' was defined as detection of viral pathogens by PCR of NP/OP specimens. CXRs were interpreted according to the WHO protocol as having 'endpoint consolidation', 'other infiltrate', or 'normal' findings. We examined associations between bacterial and viral infections and endpoint consolidation.Urine antigen and/or blood culture results were available for 721 patients with CXR interpretations; of these, 385 (53%) had endpoint consolidation and 253 (35%) had other infiltrate. Any bacterial infection was detected in 119 (17%) patients, including 106 (89%) pneumococcal infections. Any bacterial infection (Diagnostic Odds Ratio [DOR] = 2.9; 95% confidence Interval (CI): 1.3-7.9) and pneumococcal infection (DOR = 3.4; 95% CI: 1.5-10.0) were associated with 'endpoint consolidation', but not 'other infiltrate' (DOR = 1.7; 95% CI: 0.7-4.9, and 1.7; 95% CI: 0.7-4.9 respectively). Viral infection was not significantly associated with 'endpoint consolidation', 'other infiltrate,' or 'normal' findings.'Endpoint consolidation' was associated with 'any bacterial infection,' specifically pneumococcal infection. Therefore, endpoint consolidation may be a useful surrogate for studies measuring the impact of interventions, such as conjugate vaccines, against bacterial pneumonia.